Prospects for the use of Blockchain Technologies in Attracting Islamic Finance to the Region - Safiullin, Marat; Elshin, Leonid; Kuznetsov, Yaroslav (Journal of Sustainable Competitive Intelligence, 2025)
Objective: This study seeks to substantiate the prospects for using blockchain technologies as a mechanism to attract Islamic finance to the Russian regions, with the dual aim of mitigating sanctions-related restrictions and fostering integration into global Islamic financial ecosystems. Methodology/Approach: The research employs econometric and systems analysis to assess the macroeconomic externalities of blockchain-driven Islamic finance inflows. A methodological toolkit was developed and tested to estimate potential market capacity, using data from four Russian regions (Tatarstan, Bashkortostan, Chechnya, Dagestan) through 2030. The approach incorporates substitution modeling of lost Western capital, scenario analysis, and the application of blockchain-based financial gateways. Originality/Relevance: The originality of this work lies in linking two underexplored areas—Islamic finance and blockchain technologies—in the context of Russia’s geoeconomic reorientation toward Asia and the Global South. The study provides an innovative framework for replacing Western capital flows with investments from Islamic finance markets through decentralized fintech solutions. Main Conclusion: Findings demonstrate that the use of blockchain-based financial mechanisms can significantly expand the capacity of Russian regions to attract Islamic finance. Tatarstan and Bashkortostan show the highest potential, while Chechnya and Dagestan present smaller but strategically relevant capacities. Blockchain solutions are positioned as a breakthrough tool for overcoming international financial isolation and enabling long-term convergence with Islamic digital ecosystems. Theoretical/Methodological Contribution: The study advances the methodological basis for assessing fintech’s role in regional investment attraction by introducing a quantitative model that integrates substitution coefficients, market capitalization ratios, and penetration indices. It enriches the theoretical discourse on blockchain’s economic externalities and provides policymakers and practitioners with actionable instruments for embedding Islamic finance within regional development strategies.